John Young Brown correspondence - Brown, John Young, 1835-1904.
ALS (1874 July 15; Henderson, Ky. or Washington, D.C.) addressed to C.C. Adams, U.S. Superintendent of Documents, in which Brown solicits documents that he is entitled to as a member of Congress.
U.S. representative from and governor of Kentucky and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, C. C. -- Correspondence; United States. -- Superintendent of Documents; Governors -- Kentucky; Lawyers; Representatives, U.S. Congress -- Kentucky